(3GdQO GdhGaQ Ydi ef RYe Cf ef Sei GHf JjejI TjN GdGSdGe cGaQs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3YHO GdhgGH Hf CMeO Hf YHO GdMb GdMfHdi s)
(3ChdgG (B:s
(3CeG HYO aEf Gddg YR hLd hdg GdfYeI GdYXei Cced gPG GdOjf hJeeg McekG hGTGQ Edi Pdc ai cJGHg GdefRd s
(3BNQgG (B:s
(3hai QOYge Cgd GdLgGdI hGdghi Yf GdCbhGd GdeDOjI GdQOjI aLRGge Gddg NjQkG Yf GdESdGe hGdeSdejf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B838s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs